An advanced CAD/CAE integration method for the generative design of face gears. (December 2018) - Wu, Yuanhang; Zhou, Yuansheng; Zhou, Zhenyu; Tang, Jinyuan; Ouyang, Hongwu
Highlights: An advanced CAD/CAE integration method is applied to design face gears. The problem of non-equidistant isoparametric discretization is solved. A comprehensive algorithm is applied to calculate the tooth surface points. Abstract: The conventional generative design of face gears involves CAD modeling and stress analysis by finite element analysis (FEA), which is usually performed repeatedly by optimizing design parameters until acceptable stress result is obtained. An integration of computer-aided design (CAD) and computer-aided engineering (CAE) can significantly reduce both time and labor costs to this generative design. However, this idea has not been adopted by any commercial software in designing face gears due to the complicated tooth surface geometry. The main problem is that the isoparametric discretization points of the tooth surface are non-equidistant. In this work, we derive an advanced method, based on the geometry characteristic of the tooth surface, to calculate the points as an even distribution on the tooth surface. In this method, sample points are discretized according to gear blank geometry and then a mapping between sample point and tooth surface point is established; according to which a comprehensive algorithm is proposed to recalculate the tooth surface points. Subsequently, the calculated tooth surface model is input to the proposed CAD/CAE integration method to implement the finite element analysis (FEA). The proposed method is validated by a series of face gear drives with varying shaft angles.